PENGARUH KERAGAMAN PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA PT CSK INSULATION ENGINEERING DI KOTA BATAM - Aristina, Aristina; Mardika, Nanda Harry (LPPM Universitas Putera Batam, 2021)
This research is intended to analyzed the influence of product diversity (X1) and service quaIity (X2) on customer loyalty (Y) at PT CSK Insulation Engineering in Batam city. This research is quantitative and data dissemination throurgh questionnaires. The sample ln this study reachead 146 through the Slovin technique, and was distributed to the customers of PT CSK Insulation Engineering in 2019 . The data collection technique in this study used nonprobability sampling, which is a sampling technique that doesn’t provide equal opportunities for each member of the population. Furthermore, the collected data were analyzed using multiple regression analysis withs the help of SPSS (Statistic Product and Service Solution) version 25. The results of this studies indicate that product diversity (X1) and service quaIity (X2) have a positive and significant impact to customer loyalty (Y) at PT CSK Insulation Engineering in Batam city. The product diversity variabIe (X1) partially has a positive and significant impact on customer loyalty (Y), the service quality variable (X2) partially has a positive and significant impact on customer loyalty (Y). Simultaneously, product diversity (X1) and service quality (X2) has a positive and significant impact on customer loyalty (Y) at PT CSK Insulation Engineering in Batam city. Keywords: Customer Loyalty; Product Diversity; Service Quality.